2010 International Conference on Field-Programmable Technology 2010
DOI: 10.1109/fpt.2010.5681495
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic scheduling Monte-Carlo framework for multi-accelerator heterogeneous clusters

Abstract: Monte-Carlo (MC) simulation is an effective tool for solving complex problems such as many-body simulation, exotic option pricing and partial differential equation solving. The huge amount of computation in MC makes it a good candidate for acceleration using hardware and distributed computing platforms. We propose a novel MC simulation framework suitable for a wide range of problems. This framework enables different hardware accelerators in a multi-accelerator heterogeneous cluster to work collaboratively on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…The clock frequency f clock = 125MHz implemented in this work and f clock = 200MHz in [5]. According to the resource utilization and the clock frequency, one can conclude that the FPGA power from this work is not more than that from the literature [5]. Even if the device powers of both works are assumed to be identical, the energy consumption can be considered roughly proportional to the execution time T s .…”
Section: B Exotic Optionmentioning
confidence: 90%
See 4 more Smart Citations
“…The clock frequency f clock = 125MHz implemented in this work and f clock = 200MHz in [5]. According to the resource utilization and the clock frequency, one can conclude that the FPGA power from this work is not more than that from the literature [5]. Even if the device powers of both works are assumed to be identical, the energy consumption can be considered roughly proportional to the execution time T s .…”
Section: B Exotic Optionmentioning
confidence: 90%
“…Of course, the result of any comparison between GPU and FPGA highly depends on the algorithms and the technology node used to manufacture the devices. For instance, Anson et al [5] demonstrated that an FPGA outperformed GPU in terms of both performance and energy, by implementing the MC method to Asian option using the Heston model. Several HLS techniques have been implemented as both research and commercial tools in recent years.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations